The single intake of levodopa modulates implicit learning in drug naïve, de novo patients with idiopathic Parkinson’s disease - Geffe, Sarah; Jende, Johann (Journal of neural transmission, 2016)
Although dopamine is known to aggravate implicit learning, the exact impact on behaviour when feedback is unavailable remains unclear. Previous studies revealed that non-rewarded learning habits are affected in long-term dopaminergic treated patients with Parkinson’s disease (PD). We studied the influence of a onetime levodopa intake on implicit learning in de novo, untreated PD patients. De novo PD patients (n = 22) before and after the single intake of levodopa and control subjects (n = 23) took part in a Go/NoGo paradigm. One stimulus was defined as target, which was first consistently preceded by one of three non-target stimuli (conditioning). This coupling was dissolved thereafter (deconditioning). In the ‘Go version’ subjects were asked to respond to the target by pressing a key, whereas in the ‘NoGo version’ response had to be inhibited. PD patients and controls (n = 14/n = 19) with an initial learning effect due to the target were included for further statistical analysis. Within the subgroup incorrect responses upon NoGo stimuli increased during the deconditioning phase. In contrast, the same patients failed to show any change after receiving 200 mg of levodopa. During the Go version, no change of the overall error rate between conditioning and deconditioning was detectable over all groups. Learning behaviour in untreated PD patients and healthy controls was indistinguishable. In contrast, the same patients varied in their implicit learning after one-time intake of levodopa, when actions had to be inhibited. Hence, the single intake of levodopa appears to modulate implicit learning behaviour in de novo PD patients.
Gesehen am 15.08.2019